Simulation study for investment decisions on the EcoBoost camshaft machining line - Ladbrook, J.; Tjahjono, Benny; Oakes, E.; de Sanabria Sales, R. R.; de Rueda, A. G.; Lizarazu, U.; Temple, Clive (Professional Engineering Publishing, 2011)
Design/redesign of manufacturing systems is a complex, risky, and expensive task. Ford Motor Company’s Valencia Engine Plant faces this challenge as it plans to upgrade its machining and assembly lines to introduce the new EcoBoost engines. The research project described in this paper aimed to support the transition process particularly at the camshaft machining line by using simulation modelling techniques. A series of experiments was carried out using the simulation model developed, and recommendations were proposed based on the results of these experiments to support the decision as to where to invest on the line. The outcomes from the research project indicated that investment is required in terms of increasing the capacity of two bottleneck operations through retooling and improving the conveyor routing logic in one key area. Keywords: simulation modelling, closed-loop network, automotive production systems
Keywords: simulation modelling; closed-loop network; automotive production systems